LEGAL SOCIALIZATION AS A BASIS FOR THE DEVELOPMENT OF THE LEGAL SOCIETY (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article examines the role, place and significance of legal socialization in the development of society. The article aims to highlight the theory and doctrine of socialization, the stages and levels of legal socialization, the stages of adaptation and internalization in the process of socialization of the individual, the object and subject of legal socialization.